Pengaruh Mutu Layanan Sarana dan Prasarana Terhadap Kepuasan Mahasiswa di Fakultas Pendidikan Teknologi dan Kejuruan Universitas Pendidikan Indonesia - Dela Purwandani; Cicih Sutarsih; Sururi . (Jurnal Tata Kelola Pendidikan, 2019)
The research titled “ The Effect Quality of Service Infrastructures to the satisfaction of students in the Faculty of Technology and Vocational Education University of Indonesia”. Issues addressed in this study is about how satisfied students are influenced by the quality of the service facilities and infrastructure. Generally, this study aims to find out the true picture regarding the quality of infrastructure services to the satisfaction of students in FPTK UPI. The method used in this research is descriptive method with quantitative approach. The technique of collecting data using questionnaires that were distributed to 96 students as the study sample. The result of the calculation using the general trend show that student satisfaction in the high category with an average score of 3.43 and quality of services in environmental infrastructure FPTK UPI included in the high category with an average score of 3.51. The correlation analysis using Pearson Product Moment, the correlation coefficient between variables X and Y is equal to 0.786 which shows that the correlation between the two variables are at high-level relations. The results of the significance test that is 12,3201,661, it means that the correlation coefficient between variables X and Y are significant with linear regression analysis equation that is: Ŷ = 9,661 + 0,806 X, this means that any change in one unit variable X will be followed by a change of variable Y for 0,806. It is concluded that there is a positive and significant relationship of Quality of Service Infrastructures on Student Satisfaction in FPTK UPI. The need to improve on the quality of service that is the responsiveness of the service while in terms of student satisfaction is the fulfillment of infrastructure for student activities.